An Adaptive Protection Technique for Smart Distribution Network - Shobole, Abdulfetah; Baysal, Mustafa; Wadi, Mohammed; Tur, Mehmet Rida (Elektronika ir Elektrotechnika, 2020)
The future distribution networks (DNs), commonly known as the smart grid is expected to be reliable, efficient, and can accommodate renewable energy resources. The smart distribution network has to withstand the technical challenges related to the integration of distributed generations (DGs). Among these technical challenges, protection malfunctioning with the increased integration of DGs is one of the important issues, which requires a great concern. Thus, a protection philosophy, which can suit the future smart grid requirements with respect to increased integration of DGs, has to be devised. In this paper, an adaptive protection technique, which is based on the characteristics of fault-current and load-current variation, is proposed. In the proposed method, intelligent electronic devices (IEDs) monitor the status of circuit breakers (CBs) and DGs. If any status change occurs, the calculation and relay agents are triggered to update the IEDs. DigSILENT PowerFactory is used to verify the suggested philosophy. Especially DigSILENT Programming Language (DPL) is used to model the adaptive protection. The solar power plant in the Antalya vicinity in Turkey is used to verify the proposed method. The results of the simulation study show the correct operation and effectiveness of the proposed method.